Model for Managing Brawling Behavior in High Schools Students - Yantri Maputra; Meria Susanti; Nila Angreiny; Izzanil Hidayati; Shasitharan Raman Kutty (HUMANISMA : Journal of Gender Studies, 2024)
Group brawls between teenage students have become recurring problem. Violence has been regarded as a solution to any problem by the adolescents. This is clear evidence that adolescents are freely carrying out anarchic acts. Indeed, this poor behavior harms not only the people engaged in the fights or brawls, but also others who are not directly involved. This research aims to describe the pattern of handling teenage brawls using grounded theory approach. The data were collected through interviews obtained from 32 informants who were selected based on the criteria predetermined by the researcher. The analysis of themes was conducted through the N Vivo 12. The results of the study identified several models of prevention, diversion, and rehabilitation to deal with the behavior of teenage brawls.